Plasma fatty acid levels and risk of non-small cell lung cancer: a large-scale prospective cohort study - Lin, Hua-Long; Lin, Qiu-Yan; Feng, Jie-Ni; Zheng, Wei-E; Yang, Chuang; Yuan, Shao-Fei (Frontiers in Nutrition, 2024)
Background Non-small cell lung cancer (NSCLC) ranks among the most prevalent and lethal malignancies globally. Fatty acids (FAs) play a significant role in diverse physiological and pathological mechanisms, yet their precise involvement in NSCLC remains poorly understood. Methods This study utilized a large-scale prospective cohort of 249,132 participants, observed over an average of 12 years, to investigate the relationship between different FAs and NSCLC risk. Analytical approaches included Cox proportional hazards regression, Kaplan–Meier survival analysis, accelerated failure time (AFT) modeling, and restricted cubic spline (RCS) analysis. Results During the follow-up period, 1,460 participants were diagnosed with NSCLC. Cox regression analysis demonstrated that elevated levels of docosahexaenoic acid (DHA), linoleic acid (LA), and omega-3 were inversely associated with NSCLC risk. Kaplan–Meier curves, along with AFT models, corroborated that elevated concentrations of DHA and LA significantly delayed NSCLC onset. Additionally, RCS analysis uncovered nuanced dose–response relationships between these FAs and NSCLC. Stratified analyses highlighted variability based on smoking status, gender, and body mass index subgroups. Conclusion The concentration of specific FAs exhibits a significant association with NSCLC risk. These results offer a foundation for devising dietary FA composition adjustments aimed at reducing NSCLC risk.